Preliminary study on the use of the bio-physico-chemical hatchery tank system for larval rearing of Lampam Jawa (puntius gonionotus). - Cheah, S. H.; Yamasaki, S.; Arumugam, Phillip T.; Ang, K. J.; Z. A, Aizam (1989)
A preliminary study on the use of the Bio-Physico-Chemical Hatchery Tank System for larval rearing of Lampam Jawa (Puntius gonionotus) at two stocking densities was conducted. In treatment A, only the main tank was used but in treatments B and C the zig-zag biostreams that were linked to the main tanks were also used. Three day old larvae measuring 3.4mm in total length and weighing 0.13mg were stocked into the tanks for treatments A,B and C at the rates of 100 larvae/m3,100 larvae/m3 and 500 larvae/m3 respectively. The water quality in the tanks and the zig-zag biostreams,phytoplankton and zooplankton development,and growth of fish larvae were monitored. The dissolved oxygen content in the tanks were usually above 5.0mg/1 and the oxygen content in the downstream portion of the biostream was usually higher than that in the upstream portion of the biostream. Even though a gradual increase in the values of nitrate-nitrogen in the tanks were observed,lower phosphate phosphorus values were observed in tanks that were linked to the biostream. The phytoplankton density in the tanks that were linked to the biostream often had values that were equal or higher than that in the tank that was not linked to the biostream. Ten days after stocking of fish larvae,the tank with higher stocking density had comparatively lower densities of macrozooplankton. Fish that were stocked at the rate of 100 larvae/m3 grew faster than fish that were stocked at the rate of 500 larvae/m3 and fish that were cultures in the tank that was linked to the biostream grew faster. The number and total weight of fry that were harvested from the tanks in treatments A,B and C were 2415 (1099g),3809 (1752g) and 7590 (885g) respectively and these values corresponded to the survival rates of 72%,88% and 35%.